Literature Review on LNG Supply Chain Risk Mapping - Muhammad Rakha Wirayuda; Imam Baihaqi; Mushonnifun Faiz Sugihartanto (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2023)
Purpose – This study aims to identify and map potential risks in the Liquefied Natural Gas (LNG) supply chain, particularly in the context of global energy transition goals set by the 2015 Paris Agreement. With increasing reliance on LNG as a primary energy source to replace coal, understanding risks that may disrupt its supply is critical for power generation systems.Methodology – A Systematic Literature Review (SLR) was conducted by collecting and screening relevant journal articles from the Scopus database. The risk identification and classification were based on the SCOR (Supply Chain Operations Reference) model, which categorizes supply chain processes into Plan, Source, Make, and Deliver. The PRISMA protocol was applied to ensure transparency and rigor in document selection and content synthesis.Findings – A total of 21 risk factors were identified and mapped across the SCOR model. The highest concentration of risks (11 out of 21) occurs in the